2005
DOI: 10.1038/sj.sc.3101834
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated resistance training in SCI individuals increases muscle fatigue resistance but not femoral artery size or blood flow

Abstract: Study design: Longitudinal. Objectives: The purpose of this study was to evaluate the effect of lower extremity resistance training on quadriceps fatigability, femoral artery diameter, and femoral artery blood flow. Setting: Academic Institution. Methods: Five male chronic spinal cord injury (SCI) individuals (American Spinal Injury Association (ASIA): A complete; C5-T10; 3675 years old) completed 18 weeks of home-based neuromuscular electrical stimulation (NMES) resistance training. Subjects trained the quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 38 publications
4
57
0
Order By: Relevance
“…The final model adjusts for weekly differences in arterial constriction % (AC%) did not find any evidence that blood velocity was altered as a result of training. 24 Furthermore, in our previous studies, we found no evidence that hyperemic blood velocity after cuff ischemia was reduced in patients with SCI versus non-disabled controls. 41,42 We do agree that future studies would benefit from measurement of blood velocity and calculation of shear rates.…”
Section: Flow-mediated Dilationmentioning
confidence: 99%
“…The final model adjusts for weekly differences in arterial constriction % (AC%) did not find any evidence that blood velocity was altered as a result of training. 24 Furthermore, in our previous studies, we found no evidence that hyperemic blood velocity after cuff ischemia was reduced in patients with SCI versus non-disabled controls. 41,42 We do agree that future studies would benefit from measurement of blood velocity and calculation of shear rates.…”
Section: Flow-mediated Dilationmentioning
confidence: 99%
“…51 With such limited data, it is difficult to interpret the value of this exercise technique. More research needs to be completed investigating [64][65][66][67][68] the acute vascular changes in response to stretch-induced contractions.…”
Section: Resultsmentioning
confidence: 99%
“…In the first study, improved quadriceps strength was found, but no improvements in femoral arterial structure or function (artery diameter, hyperemic response, exercise blood flow response). 68 In the follow-up study from the same group, improved femoral artery flow-mediated dilatation was elevated after the training regimen. 67 Another study performed by Taylor et al, 24 which used a progressive 3-month long knee extension exercise with the aim of allowing standing, illustrated increased muscle thickness and thigh blood flow.…”
Section: Exercise Training Interventionsmentioning
confidence: 90%
See 2 more Smart Citations